Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/rs70810295
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Aquatic Vegetation in a Large, Shallow Eutrophic Lake: A Frequency-Based Approach Using Multiple Years of MODIS Data

Abstract: Aquatic vegetation serves many important ecological and socioeconomic functions in lake ecosystems. The presence of floating algae poses difficulties for accurately estimating the distribution of aquatic vegetation in eutrophic lakes. We present an approach to map the distribution of aquatic vegetation in Lake Taihu (a large, shallow eutrophic lake in China) and reduce the influence of floating algae on aquatic vegetation mapping. the 11 years. Our findings suggest that (1) the proposed approach can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Previous studies have shown that submerged aquatic vegetation is also beneficial to the improvement of water quality by the weakening of wind-induced waves, which inhibits sediment resuspension and internal nutrient release [8,18,44]. Therefore, the result further confirmed a positive feedback between SDD and submerged aquatic vegetation.…”
Section: Reciprocal Relationship Between Sdd and Aquatic Vegetationsupporting
confidence: 66%
See 2 more Smart Citations
“…Previous studies have shown that submerged aquatic vegetation is also beneficial to the improvement of water quality by the weakening of wind-induced waves, which inhibits sediment resuspension and internal nutrient release [8,18,44]. Therefore, the result further confirmed a positive feedback between SDD and submerged aquatic vegetation.…”
Section: Reciprocal Relationship Between Sdd and Aquatic Vegetationsupporting
confidence: 66%
“…In view of the fact that aquatic vegetation can counteract wind-driven waves, filter particulate matter, and prevent sediment resuspension [8], it is also an important factor that influences water transparency [43]. Therefore, we introduced the vegetation presence frequency (VPF) calculated from the floating algal index (FAI) to capture the temporal and spatial distribution of aquatic vegetation in turbid waters [44]. The FAI was proposed by Hu et al for detecting cyanobacteria and floating vegetation in waters [45].…”
Section: Satellite Data Acquisition and Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmful cyanobacterial scums regularly occur in the northern Meiliang, Zhushan, and Gonghu bays and on the western lakeshore [19]. The eastern and southern lake areas are characterized by extensive areas of macrophytes, where turbidity is low and cyanobacterial scums are rare [68,79]. Thus many researchers always divided Lake Taihu into cyanobacteria-dominated zone and a macrophytes-dominated zone [64][65][66].…”
Section: Lake Taihumentioning
confidence: 99%
“…In total, the overall classification accuracy and normalized accuracy was almost similar, 86.0% and 86.8% respectively. The classification accuracy was influenced by: the number and spatial distribution of ground-truth data [68] and the spatial resolution of MODIS where mixed pixels effects could lower the overall accuracy. …”
Section: Validation By Field Investigationmentioning
confidence: 99%